Distinct Regulatory Proteins Control the Graded Transcriptional Response to Increasing H(2)O(2) Levels in Fission Yeast Schizosaccharomyces pombe - Quinn, Janet (The American Society for Cell Biology, 2002)
The signaling pathways that sense adverse stimuli and communicate with the nucleus to initiate appropriate changes in gene expression are central to the cellular stress response. Herein, we have characterized the role of the Sty1 (Spc1) stress-activated mitogen-activated protein kinase pathway, and the Pap1 and Atf1 transcription factors, in regulating the response to H(2)O(2) in the fission yeast Schizosaccharomyces pombe. We find that H(2)O(2) activates the Sty1 pathway in a dose-dependent manner via at least two sensing mechanisms. At relatively low levels of H(2)O(2), a two component-signaling pathway, which feeds into either of the two stress-activated mitogen-activated protein kinase kinase kinases Wak1 or Win1, regulates Sty1 phosphorylation. In contrast, at high levels of H(2)O(2), Sty1 activation is controlled predominantly by a two-component independent mechanism and requires the function of both Wak1 and Win1. Individual transcription factors were also found to function within a limited range of H(2)O(2) concentrations. Pap1 activates target genes primarily in response to low levels of H(2)O(2), whereas Atf1 primarily controls the transcriptional response to high concentrations of H(2)O(2). Our results demonstrate that S. pombe uses a combination of stress-responsive regulatory proteins to gauge and effect the appropriate transcriptional response to increasing concentrations of H(2)O(2).